Keragaman dan Potensi Pemanfaatan Vegetasi Gulma Pasca Pertanaman Padi di Desa Penggaron Kecamatan Mojowarno Kabupaten Jombang - Anggi Indah Yuliana; Mucharommah Sartika Ami (SAINTEKBU, 2021)
A field study aims to determine the diversity and potential utilization of weed vegetation that grows after rice planting. This research was carried out in paddy fields after monoculture rice planting in Penggaron Village, Mojowarno District, Jombang Regency in July - September 2020. Sampling was based on the quadratic sampling method with sample plots arranged randomly. In each plot the data taken is the name, number and canopy (area of ​​cover) of each plant species to determine density, dominance and frequency. Data analysis includes vegetation analysis to determine Summed Dominance Ratio (SDR) and biodiversity analysis calculated using the Shannon - Wienner diversity index. The results of this study were 26 types of weed vegetation were found in post-rice planting land. The dominant vegetation types include Oryza sativa L .; Limnocharis flava (L.) Buchenav; Phyllanthus urinaria L .; Monochoria vaginalis (Burm.f.) pressl; and Cleome viscosa L with an SDR value of ≥ 5.30%. A total of 15 types of weeds have the potential to be used as a source of food, animal feed, and traditional medicine.